Study on Business Administration Problems and Countermeasures of Rural Enterprises in the Context of Rural Revitalization - Huang, Heng (Transactions on Economics, Business and Management Research, 2024)
The general requirements of the rural revitalization strategy pay more attention to the overall development of rural areas and have richer connotations. Industrial prosperity means promoting industrial development, attracting a large amount of capital, advanced technology and talents into the countryside, promoting the industrial development of the countryside by mobilizing the production enthusiasm and creativity of farmers, forming a vibrant rural industrial system, and realizing the modernization of the countryside and the modernization of agriculture. In the context of rural revitalization, business administration innovation in rural enterprises has become an important way to enhance the comprehensive strength and core competitiveness of enterprises. However, enterprise business administration innovation also faces a series of problems and challenges, such as the lack of innovative elements in enterprise culture, imperfect talent training mechanism, high cost of technological innovation, and insufficient sense of win-win cooperation among enterprises.